The vision of bioethical principles regarding immunization (Research, Society and Development, 2022)
Advances in science have made many contributions to human development. Vaccines are one of the best examples of this, working as a tool capable of preventing infectious diseases. Objective: to analyze the principles of bioethics regarding the offer of vaccination to the population. Method: This is an integrative literature review, carried out through a survey of studies published in databases of the Electronic Science Library Online (ScIELO), Virtual Health Library (BVS), Brazilian Journal of Nursing (REBEn), in the period from 2016 to 2022. Results. The different authors discussed the relationship between the offer of mass vaccination and bioethics, showing that this practice can lead to non-observance of bioethical principles, since the common good that is the fact of offering immunization to all, can be understood as respect for the principle of justice, more than it can directly interfere with the principle of individual autonomy, since compulsory vaccination is defended based on the principle that, in the scope of collective health, the protection of the population must prevail over the autonomy of the individual. However, for this, the vaccine needs to have its effectiveness proven, in order to respect the principle of beneficence and non-maleficence in the act of its application. Conclusion: One of the ways to ensure respect for bioethical principles regarding vaccination is to choose the path of health education for the population so that they can understand the importance and make their own choices, thus respecting the bioethical principle of autonomy.